PERAN SOSIALISASI DALAM MEMEDIASI PENGARUH PERSEPSI DAN SIKAP BURUH TERHADAP PARTISIPASI PADA LAYANAN PROTEKSI KETENAGAKERJAAN - Yundhari, Trisna; Marhaeni, A.A.I.N; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.08.TAHUN 2018DO - 10.24843/EEB.2018.v07.i08.p05, 2018)
This research is a qualitative and quantitative research which is analyzed in descriptions by describing or describing the collected data conducted in Blahbatuh District, Gianyar Regency. Analytical techniques of this study using two methods of data analysis. First, by using factor analysis methods to describe a state or a concept, the planned variables will be treated as indicators of either the latent independent variable or the latent dependent. Secondly, by using path analysis method to know the relationship pattern between three or more and can not be used to confirm or reject the hypothesis. The sample used in this study were 99 respondents. The result of the analysis shows that the level of labor participation is seen from labor perception indicator, labor attitude, and socialization participation in Blahbatuh sub-district, Gianyar regency is positive. This is seen from the average score obtained from each indicator, labor perception, labor attitude, and socialization of labor, and labor participation. Indirectly, workers' perceptions and worker attitudes have a positive and significant influence on participation in labor protection services to explore the participation of socialization in labor protection services in Blahbatuh sub-district, Blahbatuh sub-district.